Haematopoietic stem cell transplantation for relapsed or refractory anaplastic large cell lymphoma: a study of children and adolescents in Japan. (14th October 2014) - Fukano, Reiji; Mori, Tetsuya; Kobayashi, Ryoji; Mitsui, Tetsuo; Fujita, Naoto; Iwasaki, Fuminori; Suzumiya, Junji; Chin, Motoaki; Goto, Hiroaki; Takahashi, Yoshiyuki; Hara, Junichi; Park, Yong‐Dong; et al.
Summary To evaluate haematopoietic stem cell transplantation (HSCT) in children and adolescents, we reviewed the records of 47 patients who were ≤18 years, had relapsed or refractory anaplastic large cell lymphoma, and received HSCT between 1990 and 2010. At HSCT, complete remission (CR) was less common in allogeneic HSCT recipients (n = 24) than in autologous HSCT recipients (n = 23) (P = 0·01). The autologous and allogeneic HSCT groups differed in terms of 5‐year event‐free survival (EFS) (38% vs. 50%, P = 0·63), cumulative incidence of progress or relapse (49% vs. 28%, P = 0·25), and treatment‐related mortality (12% vs. 25%, P = 0·40). However, these differences were not significant. Patients with non‐CR at autologous HSCT had a significantly lower EFS rate (14% vs. 48%, P = 0·03). Conversely, although those with non‐CR at allogeneic HSCT had a lower EFS rate, this was not significant (44% vs. 63%, P = 0·26). Reduced‐intensity conditioning regimens were used for three of the 16 allogeneic HSCTs received by patients with non‐CR. These three patients achieved CR, surviving 32–65 months after HSCT. These results demonstrated that allogeneic HSCT might be a treatment option for patients who do not achieve CR through conventional chemotherapy.